Clinical Profile of Unilateral Proptosis in a Tertiary Care Centre - Susan Dsouza; Pooja Kandula; Gurudutt Kamath; Manjunath Kamath (Journal of Ophthalmology)
Proptosis, the forward protrusion of the eyeball, is a common manifestation of a wide variety of diseases inside the orbit and its spaces. Its diagnosis is usually a combined effort of the ophthalmologist, otolaryngologist, neurosurgeon, and radiologist. A clinical study of twenty-five cases with unilateral proptosis were studied in different age groups over a period of about 3 years under different headings like distribution, clinical features, radiological features, histopathological aspects, management, and outcomes of diseases. Proptosis measurement was done by simple/plastic ruler exophthalmometry, and diagnosis was made after a detailed clinical examination and ancillary tests. Treatment modality was decided based on radiological and histopathological examination reports, which included medical surgery, radiotherapy, and chemotherapy or a combination of all. In our study, most of the patients were in the age group of more than 60 years. The M : F ratio is 3 : 1. One case had a large proptosis of 18 mm above normal and 2 cases were as small as 3 mm. Diagnosis was mainly done by clinical features and confirmed by radiological and histopathological features. Most of them were treated medically (13 cases, i.e., 52%) and the rest by surgery with a combination of radiotherapy/chemotherapy (12 cases, i.e., 48%).